Endoscopic stricturotomy and ileo-colonic resection in patients with primary Crohn's disease-related distal ileum strictures. (5th February 2020) - Lan, Nan; Hull, Tracy L; Shen, Bo
Abstract: Background: Stricture is a common presentation of Crohn's disease with the site of prevalence being the distal ileum. This study aimed to compare the efficacy and safety of patients with primary distal ileum stricture treated with endoscopic stricturotomy (ESt) vs ileo-colonic resection (ICR). Methods: All consecutive patients with primary distal ileum stricture that were treated with ESt and/or ICR were extracted from the interventional inflammatory bowel disease ( i -IBD) unit from 2001 to 2016. All patients with a stricture >5 cm or those with anastomotic strictures were excluded from the study. The primary outcomes were surgery-free survival and post-procedural complications. Results: A total of 13 patients receiving ESt and 32 patients receiving ICR were included in this study. Although the length of the stricture is comparable between the two groups (2.4 ± 0.9 vs 3.0 ± 1.1 cm, P  =   0.17), patients who received surgery had a more complicated obstruction presented by the high pre-stenosis proximal dilation rate (67.7% vs 9.1%, P  =   0.001). All patients in both groups achieved immediate technical success after treatment. The median follow-up durations were 1.8 and 1.5 years in the ESt and ICR groups, respectively. The subsequent surgery rates were similar between the two groups (15.4% vs 18.8%, P  =   0.79) and the overall surgery-free survival was also comparable between the two groups ( P  =   0.98). Post-procedural adverse events were seen in 2/29 ESt procedures (6.9% per procedure) and 8/32 (25.0%) patients receiving ICR ( P  =   0.05). Conclusions: ESt achieved comparable stricture-related surgery-free survival as ICR, while ESt had a numerically lower post-operative complication rate.